BIPOLAR AFFECTIVE DISORDER AND MANIC EPISODE WITH PSYCHOTIC SYMPTOMS IN A 39 YEARS OLD MAN - Lewi Martha Furi (Fakultas Kedokteran Universitas Lampung, 2014)
Bipolar is a mood disorder that consists at least one manic episode, hypomania, or mixed which is usually accompanied by a history of major depressive episodes. An extreme shift of mood, motivation, and energy suffered by patients with bipolar can lead to disability and even suicide. Therefore, it is important to know the symptoms, how to diagnose, and the treatment. A man, 39 years old, came with his family with the complaint of rampage and beating people for no reason. Over the past month, the family admitted patients cannot sleep. On physical examination found cuts on the right cheek. General status, neurological, and laboratory tests are in normal range, from psychiatric examination obtained clear consciousness, elevation of mood occasionally disforic, blunted affect, Inappropriate, with auditory, tactile, and visual hallucinations accompanied with delusions of greatness and erotomaniac. Patients diagnosed with axis I: F31.2 bipolar affective disorder, manic episode with psychotic symptoms; axis II: notfound yet; axis III: vulnus laceratum in the right maxillary region; axis IV: primary support group problems; axis V: GAF20-11. Pharmacotherapy with haloperidol 3x2 mg tab, clozapine 2x25 mg tab, and supportive psychotherapy. Bipolar disorder in these patients was initiated after his wife passed. [J Agromed Unila 2014; 1(3):211-215]Keywords: bipolar, hallucination, man ,manic, phsycotic